The Relationship between Self-Control and Work Discipline for the Tanah Datar Communication Service Employees After the Covid -19 Pandemic - Permata, Inayah; Zulfikar, Zulfikar; Yoselisa , Dani; Erkka, Karajamaki (Yayasan Minang Darussalam, 2023)
The main problem in this research is the problem of employee self - control in the world of work . The purpose of this study was to determine the relationship between self-control and work discipline of employees of the Flat Land Communications and Information Service after the Covid- 19 pandemic . The type of research used is a correlational quantitative type. The population in this study were 54 communications and information service employees . The type of sampling is total sampling . The results showed that there was no significant relationship between self-control and the work discipline of the employees of the Flat Land Communication and Information Service. The data obtained showed that the correlation coefficient was r -0.093 with a significance of 0.503 ( p > 0.05), which means the hypothesis in this study Ha rejected and Ho accepted. With this the researchers obtained the result that there was no negative or significant relationship between self-control and work discipline of employees of the Tanah Datar communications and information service after the Covid- 19 pandemic